The Novel Medical Thermoresponsive Hydrogel Derived from Chitosan - Kong, Ming; Chen, Xiguang (Current Organic Chemistry, 2018)
Background: Chitosan thermoresponsive hydrogel is non-covalent crosslinked intelligent hydrogel. The compositions of the hydrogel determine its gelling property associated with particular structure-interaction effects. Simple and mild preparations as well as desirable bioactivities allow chitosan thermoresponsive hydrogels extensively applied in drug delivery and tissue engineering, especially the exciting proceeding in enzyme-free cell harvest and vascular embolic agent. Objective: This paper reviewed the classification of chitosan thermoresponsive hydrogels based on different components, emphasizing their gelling capacities, mechanism and applications in biomedical areas.
Keywords: sol-gel reversible